Castigo para los buenos : el tercer caso del sheriff Walt Longmire - Johnson, Craig, 1961- (Nuevos tiempos (Madrid, Spain) ;, 2014)
Walt Longmire has been sheriff of Wyoming's Absaroka County for almost a quarter of a century and has meted out justice with charm and a high-powered sense of humor. But when Walt tags along with good friend Henry Standing Bear on a trip to Philadelphia, he's in for a shock. A vicious attack on his daughter Cady leaves her near death and Walt discovers that she has unwittingly become embroiled in a deadly political cover-up. With Henry, Deputy Victoria Moretti, the entire Moretti clan of Philadelphia police officers, and Dog as backup, Sheriff Longmire intends to introduce a little western justice from his saddlebag of tricks to the City of Brotherly Love, where no act of kindness goes unpunished.